Environmental & architectural phenomenology. Vol. 15, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2004)
Vol. 15, No. 2, Spring 2004 (includes “items of interest,” “citations received,” critique of J.E. Malpas' Place and Experience, and essays by Shierry Weber Nicholsen & R. Murray Schafer).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals